THE REALITIES OF PROFESSIONAL ETHICS. - Carey, John L. (The Accounting Review, 1947)
The article focuses on the importance of professional ethics in accounting. Many accounting teachers have recognized the desirability of including professional ethics as part of the subject matter of instruction of students who are preparing for the professional practice of public accounting. However not much has been done about it. It is good form to talk about the importance of ethics but subconsciously many practitioners and some teachers too are disposed to consider the subject of little practical significance. There is a disposition to relegate ethics, as a subject for active study and discussion, to that pigeonhole reserved for the abstractions which it is diverting to talk about in leisure time, but which are of no immediate concern in the daily business of life. This is a sad mistake. Leaders of the profession recognize and are saying with increasing frequency, that the future opportunities of public accountants depend on maintenance of public confidence. There is much more talk about public relations and public information but the codes of professional ethics and their enforcement are an essential part of the foundation for good public relations.